2012
DOI: 10.1021/jf204361d
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of La Rioja Terroir for Wine Production Using 1H NMR Metabolomics

Abstract: In this study, La Rioja wine terroir was investigated by the use of (1)H NMR metabolomics on must and wine samples. Rioja is a small wine region in central northern Spain which can geographically be divided into three subareas (Rioja Alta, Rioja Baja, and Rioja Alavesa). The winemaking process from must, through alcoholic and malolactic fermentation, was followed by NMR metabolomics and chemometrics of nine wineries in the Rioja subareas (terroirs). Application of interval extended canonical variate analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 39 publications
3
84
0
Order By: Relevance
“…Growing regions can be distinguished based on the abundance of several key fungal and bacterial taxa, defining potentially predictive regional features with obvious consequences for grapevine management and wine quality. The chemicosensory distinction of wines from different growing regions is well established (29)(30)(31)(32)(33), providing the conceptual basis of wine terroir, although the causative factors are elusive (9). Likewise, the formative influences of many key grape-derived microbiota on wine quality Significantly discriminant taxon nodes are colored and branch areas are shaded according to the highest-ranked variety for that taxon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing regions can be distinguished based on the abundance of several key fungal and bacterial taxa, defining potentially predictive regional features with obvious consequences for grapevine management and wine quality. The chemicosensory distinction of wines from different growing regions is well established (29)(30)(31)(32)(33), providing the conceptual basis of wine terroir, although the causative factors are elusive (9). Likewise, the formative influences of many key grape-derived microbiota on wine quality Significantly discriminant taxon nodes are colored and branch areas are shaded according to the highest-ranked variety for that taxon.…”
Section: Resultsmentioning
confidence: 99%
“…As the most dominant and discriminant taxa between regions and varieties have well-characterized impacts on grape and wine qual- ities, these differences may help explain regional patterns in wine chemicosensory properties (29)(30)(31)(32)(33). Whether these regionally differential microbiota actually modulate wine sensory qualities must be experimentally tested, as do all putative features of wine terroir.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic profiles contain information about the levels of large numbers of metabolites. They provide an integrative phenotype that has already been shown to be predictive of biomass yield [16][17][18] , heterosis 19 and, to a lesser extent, abiotic stress tolerance 20 , as well as to be indicative of wine quality from different sites [21][22][23] . We analysed the levels of 49 metabolites in 92 diverse accessions, including lines with different growth habitats and geographic origins (Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…López-Rituerto et al [50] investigated the La Rioja wine terroir using 1 H NMR metabolomics of must and wine samples obtained from different wineries located in this area of central Spain, reporting that the aliphatic alcohols isopentanol and isobutanol were key biomarkers for H NMR metabolomics has also been used to characterize the terroir effect on the quality of Aglianico red wines from the Campania region of Italy [14]. Multivariate analysis of the NMR metabolite data demonstrated that the differentiation observed among wines produced from three different vineyards was related to microclimate and the carbonate, clay, and organic matter content of soils.…”
mentioning
confidence: 99%